2015
DOI: 10.1302/0301-620x.97b2.35248
|View full text |Cite
|
Sign up to set email alerts
|

Cause of death and factors associated with early in-hospital mortality after hip fracture

Abstract: The aims of this study were to identify the early in-hospital mortality rate after hip fracture, identify factors associated with this mortality, and identify the cause of death in these patients. A retrospective cohort study was performed on 4426 patients admitted to our institution between the 1 January 2006 and 31 December 2013 with a hip fracture (1128 male (26%), mean age 82.0 years (60 to 105)). Admissions increased annually, but despite this 30-day mortality decreased from 12.1% to 6.5%; 77% of these we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
65
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 20 publications
10
65
2
8
Order By: Relevance
“…In this study, we found, firstly, that in-hospital mortality did not differ between aged and advanced age groups, which was confirmed by a univariate analysis and binominal multivariate logistic regression analysis, secondly, that in-hospital morality was low in both groups as compared to the reported values [1,2], and, thirdly, that most patients died from advanced cancer or aspiration pneumonia.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In this study, we found, firstly, that in-hospital mortality did not differ between aged and advanced age groups, which was confirmed by a univariate analysis and binominal multivariate logistic regression analysis, secondly, that in-hospital morality was low in both groups as compared to the reported values [1,2], and, thirdly, that most patients died from advanced cancer or aspiration pneumonia.…”
Section: Discussionsupporting
confidence: 73%
“…First, the in-hospital mortality in this study was less than that previously reported from western countries. Even in those studies, the odds ratio of age among patients aged over 70 years is relatively small [1,6]. Age should thus be considered as a risk only at the extremes of age, i.e., over 95 years [7].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The co-existence of significant comorbidities, dementia and difficulties in pain management constitute the medical management of these patients challenging [3][4][5]. Despite recent advances in surgical and medical management of elderly patients with hip fractures latest relevant research has shown that the one year post-injury associated mortality is still high ranging from 18.8% to 22.8% and increases with age [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%